Calcium phosphate coatings produced by radiofrequency magnetron sputtering method; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Bolbasov E. N. Evgeny Nikolaevich; Zheravin A. A.; Klimov I. A.; Kulbakin D. E.; Perelmuter V. M.; Tverdokhlebov S. I. Sergei Ivanovich; Cherdyntseva N. V.; Choinzonov E. L. (2016, 2016)
Title screen